Development of eccentric driven transmission system for garden tractor - ANVUR V. A JAYAPRADEEP S SATHEESAN M. M; Prof. C. P Muhammad (Guide) (Tavanur 1998 Department of Farm Power Machinery and Energy)
low cost garden tractor.single phase v-belt drive, an eccentric assembly, a connecting link, an oscillating line and an intermediate shaft. backward motion.
Development of eccentric driven transmission system for garden tractor